Economic Analysis: Green Hydrogen Production Systems - Chavez-Orostica, H (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The continued use of energy sources based on fossil fuels has various repercussions for the environment. These repercussions are being minimized through the use of renewable energy supplies and new techniques to decarbonize the global energy matrix. For many years, hydrogen has been one of the most used gases in all kinds of industry, and now it is possible to produce it efficiently, on a large scale, and in a non-polluting way. This gas is mainly used in the chemical industry and in the oil refining industry, but the constant growth of its applications has generated the interest of all the countries of the world. Its use in transportation, petrochemical industries, heating equipment, etc., will result in a decrease in the production of greenhouse gases, which are harmful to the environment. This means hydrogen is widely used and needed by countries, creating great opportunities for hydrogen export business. This paper details concepts about the production of green hydrogen, its associated technologies, and demand projections. In addition, the current situation of several countries regarding the use of this new fuel, their national strategy, and advances in research carried out in different parts of the world for various hydrogen generation projects are discussed. Additionally, the great opportunities that Chile has for this new hydrogen export business, thanks to the renewable energy production capacities in the north and south of the country, are discussed. The latter is key for countries that require large amounts of hydrogen to meet the demand from various industrial, energy, and transportation sectors. Therefore, it is of global importance to determine the real capacities that this country has in the face of this new green fuel. For this, modeling was carried out through mathematical representations, showing the behavior of the technologies involved in the production of hydrogen for a system composed of an on-grid photovoltaic plant, an electrolyser, and compressor, together with a storage system. The program optimized the capacities of the equipment in such a way as to reduce the costs of hydrogen production and thereby demonstrate Chile’s capacity for the production of this fuel. From this, it was found that the LCOH for the case study was equivalent to 3.5 USD/kg, which is not yet considered a profitable value for the long term. Due to this, five case studies were analyzed, to see what factors influence the LCOH, and thereby reduce it as much as possible. © 2023 by the authors.